IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA (PERSERO) REFINERY UNIT II DUMAI PADA PROGRAM PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN CORPORATE IMAGE - Debby Wulandari; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Corporate Social Responsibility or CSR is basically a company commitment to give long term contribution to society or environment to create better environment. Good CSR implementation will generate public trust to the company, then a positive image will be able to be improved by the company. This study aims to determine the stage-by-stage implementation of CSR program by PT. Pertamina RU II Dumai in improving corporate image as well as the forms of community empowerment program of CSR PT. Pertamina RU II Dumai in improving corporate image.This research uses qualitative research method with descriptive approach. Research subject consisted of 9 informants selected through purposive technique. Data collection is done through observation, interview and documentation. To test the validity of data writer used extension method of participation and triangulation.The result of this study indicates that in implementing the program, the stages that CSR RU II has undergone are planning, implantation and evaluation. CSR program by PT. Pertamina RU II in the field of community empowerment are the development of integrated agricultural areas, the development of farmer groups, empowerment of women, and empowerment of youth. These four programs are effective enough to establish community, increase people’s economic income and increase community’s awaresness of the environment. Then there is exhibition program of the target groups and partners of CSR RU II which is effective in the effort to publicize CSR support group to the community as well as effort in improving the corporate image.Keyword: Implementation, Corporate Social Responsibility, Corporate Image.